ERBB3 is required for tumor promotion in a mouse model of skin carcinogenesis. Issue 9 (3rd July 2015) - Dahlhoff, Maik; Schäfer, Matthias; Muzumdar, Sukalp; Rose, Christian; Schneider, Marlon R.
Abstract : The epidermal growth factor receptor (EGFR) plays a key role in skin inflammation, wound healing, and carcinogenesis. Less is known about the functions of the structurally related receptor ERBB3 (HER3) in the skin. We assessed the requirement of ERBB3 for skin homeostasis, wound healing, and tumorigenesis by crossing mice carrying a conditional Erbb3 allele with animals expressing cre under the control of the keratin 5 promoter. Erbb3del mice, lacking ERBB3 specifically in keratinocytes, showed no obvious abnormalities. The EGFR was upregulated in Erbb3del skin, possibly compensating the loss of ERBB3. Nonetheless, healing of full‐thickness excisional wounds was negatively affected by ERBB3 deficiency. To analyze the function of ERBB3 during tumorigenesis, we employed the established DMBA/TPA multi‐stage chemical carcinogenesis protocol. Erbb3del mice remained free of papillomas for a longer time and had significantly reduced tumor burden compared to control littermates. Tumor cell proliferation was considerably reduced in Erbb3del mice, and loss of ERBB3 also impaired keratinocyte proliferation after a single application of TPA. In human skin tumor samples, upregulated ERBB3 expression was observed in squamous cell carcinoma, condyloma, and malignant melanoma. Thus, we conclude that ERBB3, while dispensable for the development and the homeostasis of the epidermis and its appendages, is required for proper wound healing and for the progression of skin tumors during multi‐stage chemical carcinogenesis in mice. ERBB3 may also be important for human skin cancer progression. The latter effects most probably reflect a key role for ERBB3 in increasing cell proliferation after stimuli as wounding or carcinogenesis. Highlights: The EGFR‐related ERBB3 receptor is dispensable for skin development and homeostasis. ERBB3 is required for wound healing and for the progression of skin tumors in mice. ERBB3 may also be important for human skin cancer progression. ERBB3 is an attractive drug target for skin cancer therapy.